REFRACTORY MATERIALS OBTAINED BY RECOVERY AND RECYCLING OF INDUSTRIAL WASTES - Luminita Georgeta POPESCU; Alexandru Traian ABAGIU; Corina COMĂNESCU (Fiabilitate şi Durabilitate)
In this paper we will present some results obtained in the industrial research works carried out on the technological flows of the industrial partner SC REFAROM SA from Brasov. The research aimed introducing in the composition of shaped refractory products (thermal insulating and antiacid refractory bricks) and unshaped (thermal insulating refractory concrete) some wastes that do not have industrial use in present (slag and ash from Rovinari CET Govora Thermal Power Plant or UATAA Motru). The experimental laboratory results revealed very good physical and mechanical properties, but especially a very good resistance of the antiacid refractory bricks to the attack with sulfuric acid of 70% concentration.